The Influence Of Leadership Style and Organizational Culture On The Employee Perpomance at PR. Hm Putra Tasikmalaya - Miftah Fauzi; Kusuma Agdhi Rahwana; Arga Sutrisna (Journal of Indonesian Management, 2022)
This study aims to determine the effect of leadership style and organizational culture on employee performance PR. Hm Putra Tasikmalaya. The method used is a quantitative approach with a reserch sample of 51 respondents from employees PR. Hm Putra Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple linear regression using SPSS version 25. The results showed that the leadership style felt by employees PR. Hm Putra Tasikmalaya had very good criteria. Organizational culture on employees PR. Hm Putra Tasikmalaya has good criteria. Simultaneously leadership style and organizational culture have a significant influence on employee performance. Partially leadership style has a significant influence on employee performance. Partially, organizational culture has a significant effect on employee performance.